1997
DOI: 10.1007/bf02407201
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead in aerosol samples collected on glass fiber filters by an improved atomic absorption spectrometry method

Abstract: Abstract. This paper presents a simple, reliable, economical, safe, accurate and reproducible method for atmospheric aerosol lead determination in glass fiber filters, consisting on an acid digestion procedure and atomic absorption spectrometry quantification. The acid digestion is accelerated by the use of a microwave oven with capped Teflon PFA vessels, and a two steps power and time program. The mixture of 10 mL HNO3 and 1 mL HF was selected between many tries, for both economic and environmental reasons. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Atomic absorption spectroscopy is the main technique used for the analysis of heavy metals in air samples, because of its selectivity, sensitivity, reproducibility, wide dynamic concentration range, and its low cost (Silvia et al 2004;Vasconcelos and Tavares 1997;Khillare et al 2004;Moreno-Grau et al 1997Bilos et al 2001;Shevchenko et al 2003;Jimmy et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Atomic absorption spectroscopy is the main technique used for the analysis of heavy metals in air samples, because of its selectivity, sensitivity, reproducibility, wide dynamic concentration range, and its low cost (Silvia et al 2004;Vasconcelos and Tavares 1997;Khillare et al 2004;Moreno-Grau et al 1997Bilos et al 2001;Shevchenko et al 2003;Jimmy et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several heavy metals have been determined in air samples in different countries such as Brazil (Silvia et al 2004), Denmark (Karl et al 2002, Portugal (Vasconcelos and Tavares 1997), India (Khillare et al 2004), Spain (Moreno-Grau et al 1997, 2000Mateu et al 1999), Egypt (Abdel-Shafy et al 1992), and Russia (Drobyshev and Emelina 2001), not to mention national and international continuous monitoring programs for regulatory purposes like the European Monitoring and Evaluation Program. Various studies have been reported in the literature regarding heavy metal concentrations in air within Indian cities (Pandit et al 2013;Jha 2010;Singh et al 2008;Dubey et al 2012;Gupta and Karar 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The application of conventional sample preparation techniques such as wet digestion in concentrated mineral acids or dry ashing in an oxygen atmosphere followed by chemical treatment results in clear solutions which can be analyzed by graphite furnace atomic absorption spectrometry (8,9), inductively coupled plasma (ICP) atomic emission (10) and mass spectrometry (11), or total reflection X-ray fluorescence (TXRF) spectrometry (12)(13)(14). To minimize contamination and losses of volatile elements, and to accelerate the digestion process, microwave-assisted digestion in sealed polytetrafluoroethylene (PTFE) bombs is highly recommended (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%